A Survey of Farmers Knowledge and Practice on the Management of Watermelon Diseases in Horticultural Belt of Mt. Kenya Slopes - Kiarie, Salome W; Imbahale, Susan S; Okoth, Sheila; Gikungu, Mary (International Journal of Sustainable Agricultural Research, 2020)
Horticulture is the largest sub-sector of agriculture, in Kenya, contributing 33% of the Agricultural GDP. Watermelon is the sixth among eight listed fruits which are economically important horticultural produce in Kenya. The fruit is grown mostly in dry areas of Kenya, however due to high demand, large acreage of land on the slopes of Mt. Kenya are now being cultivated with this crop. A study was carried out in July 2018 to examine watermelon farmers’ knowledge and practice in the management of watermelon diseases on the slopes of Mt. Kenya. A semi-structured questionnaire was administered to 80 watermelon farmer’s selected using Snowball technique from Karurumo, Gachoka, Kiritiri and Ishiara locations. The survey revealed that majority of farmers grew watermelon on 1-2 acres. Watermelon diseases were reported to attack the plant at all stages of growth. Among the diseases, blight was reported by most respondents at 63.8%, followed by fusarium wilt (41.3%) and powdery mildew (38.8%). Farmers experience of various diseases was not significantly different in the four locations except for Fusarium wilt (p=0.046) and powdery mildew (p=0.020). Cold weather was reported by 60% of respondents as most conducive condition for disease occurrence, followed by rainy conditions (17.5%). Most farmers in all the locations applied pesticides (97.6%) as the major method of disease control, with a few (27.5%) practicing crop rotation. This was attributed to agronomic support by extension workers in the area. The slopes of Mt. Kenya, have potential of increased production only if farmers receive support in disease management.